1997
DOI: 10.1152/ajpendo.1997.272.6.e1043
|View full text |Cite
|
Sign up to set email alerts
|

Adenylyl cyclase inhibitory pathway is differentially modified in rat white and brown fat by high-energy diets

Abstract: Incubation of white adipose tissue (WAT) adipocytes from rats fed a high-energy diet (Exp group) with antilipolytic Gi-coupled adenylyl cyclase inhibitory agonists, nicotinic acid (Nic) and N8-(L-2-phenylisopropyl)adenosine (PIA), resulted in lower cellular adenosine 3',5'-cyclic monophosphate (cAMP) levels than in stimulated adipocytes from rats fed a nutritionally balanced diet (Con group). In contrast to WAT, incubation of brown adipose tissue (BAT) adipocytes with Nic yielded higher cAMP levels in the Exp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The level of expression of G-proteins is sensitive to both the nutritional and hormonal states of the organism (24). Alterations in adenylyl cyclase activity in response to high-energy diets (42) as well as in hypothyroidism (43)(44)(45) have been reported. Furthermore, the mechanism of action disentangled here may be applied not only to lipid metabolism regulation, but also to glucose homeostasis and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The level of expression of G-proteins is sensitive to both the nutritional and hormonal states of the organism (24). Alterations in adenylyl cyclase activity in response to high-energy diets (42) as well as in hypothyroidism (43)(44)(45) have been reported. Furthermore, the mechanism of action disentangled here may be applied not only to lipid metabolism regulation, but also to glucose homeostasis and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Such a study is important, since recent studies have indicated differential modi®cation of white-and brown-adipose-tissue glucose transport and intracellular signalling mechanisms by high-fat feeding. 36,37 We examined white adipose tissue from several depots in view of data demonstrating that individual depots subserve distinct physiological functions and may exhibit differential sensitivities to insulin (see for example, Refs 38 ± 41).…”
Section: Discussionmentioning
confidence: 99%
“…In experiments using fat cells from young pigs, it was shown that feeding these animals feeds with the addition of maize starch caused a distinct rise in lipogenesis stimulated by insulin (Smith et al, 1996). It was also observed that excess energy in food may contribute to a reduction in the amount of cAMP and restriction of lipolysis in fat cells (Kenan et al, 1997).…”
Section: Hormonal Regulationmentioning
confidence: 99%